ALIH KODE DAN CAMPUR KODE DALAM LIRIK LAGU DALAM LIRIK LAGU - , HARI SANGA; , Amin Basuki, SS., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to describe the type, form and the reason for code switching and code mixing in Big Bangâs song lyrics. The research method used in this research is descriptive method. Data consist of quotations of some lines found in Big Bangâs song lyrics which have code mixing and code switching. Data were analyzed by classifying into code swtiching and code mixing in accordance with Suwitoâs theory (1983), Poklack (via Kurniawati dkk. 2012), and Poedjosoedarmo (1978). The result of the data analysis shows that type of code switching found in the Big Bangâs song lyrics are external code switching. Code switching which occured are in the form of intersentential switching and intrasentential switching. The reason of the occurence of code switching in Big Bangâs song lyrics is by adjusting the language code mastered by the interlocutor, the inability to use language code which is being used for a long time constantly, the change of interlocutor, and the particular intentions of the speaker. The type of code mixing which appears is outer code switching. Code mixing which occured in the Big Bangâs song lyrics are in the form of inserting word, phrase, clause, and reduplication. The reason of code mixing in Big Bangâs song lyrics are: (1) caused by the elements of language which is inserted are more commonly used, (2) to give the impression of authority, (3) to expand the language style, (4) to show that the song writer and singer master many languages, (5) to express distrust, (6) to express a request, (7) to express a shock, (8) to express the meaning of the sentence and (9) to harmonize the sound and rhythm.